Theories of public organization - Denhardt, Robert B. (Thomson/Wadsworth, 2008)
[This text includes] material on feminist thought, civic engagement, postmodernism, and the ethics of public service. [It also] focus[es] on the current debate in public administration around the differences between the New Public Management and ... New Public Service. [This] is a book about theory but also about practice. It is written to introduce theories of public organization to students of public administration and to those outside the field who wish to involve themselves in organizations committed to public purposes. More important, this book is an attempt to develop a critique of the mainstream literature in public administration theory based on its inability to connect with the real experiences of those working in and with public organizations. -Pref.